High-quality petroleum-like fuels and/or profitable value-added platform chemicals manufactured via a solid acid-catalyzed two-stage fast oil shale pyrolysis. (15th July 2023) - Xu, Guojing; Ren, Zhaoyang; Cui, Lijie; Wang, Zhenpeng; Wang, Nannan; Li, Peng; Guan, Bo; Qin, Xujin; Chen, Penglei
Graphical abstract: A novel protocol for an efficient and profitable thermochemical conversion of oil shale has been proposed, where either high-quality petroleum-like fuels or several kinds of value-added platform chemicals of broad academic and engineering interests, including thiophenes (particularly, 2-methylthiophene), α -olefins (especially, 1-hexene and 1-heptene), and toluene, could be preferentially manufactured via a solid acid-catalyzed two-stage flash pyrolysis. The strength/concentration of Brønsted acids of the catalyst is stronger/higher than that of Lewis acids such that their synergistic-competitive effects direct the thermochemical reactions to occur preferentially along specific paths, endowing the catalyst with outstanding catalytic performances. Abstract: Catalyst-assisted oil shale (OS) pyrolysis has gained broad interest from academic/engineering communities. However, current state-of-the-art catalysts still face many problems, e.g., laborious fabrication, unsatisfactory selectivity, etc . Taking commercial titanium(IV) oxysulfate solid acid (TOSSA) as an example and using a two-stage flash pyrolysis protocol, we report that when TOSSA-assisted pyrolysis is conducted at the first shot (438 °C), the content of N-, O-containing compounds and medium/long-chain aliphatic hydrocarbons (M/LCAHCs), undesirable for petroleum-like fuels (PLFs), decreases by 41.2%, 36.5% and 22.7%, respectively. The content of hydrocarbons (HCs), which is beneficial for PLFs, increases by 12.9%, where that of short-chain aliphatic HCs (SCAHCs, ≤C13), which are desired for light PLFs, increases by 285.7%. The content of α -olefins, valuable tectons for polyolefins, increases from 0% to 6.4%. Fascinatingly, the content of thiophenes, refractory heteroatomic species for PLFs but valuable tectons used in flexible/foldable optoelectronics, increases by 329.7%. For the second shot (590 °C), heteroatomic compounds content declines by 36.5%, HCs content increases from 69.3% to as high as 80.5%, where SCAHCs and M/LCAHCs content increases and declines by 39.7% and 27.1%, respectively. The content of toluene, important species in chemical science/engineering, increases by 237.5%. The content of 1-hexene and 1-heptene, overwhelming precursors for functional molecules/materials, increases by 210.0% and 412.5%, respectively. The strength/concentration of Brønsted acids of TOSSA is stronger/higher than that of Lewis acids such that their competitive-synergistic effects might endow TOSSA with good catalytic performances.